Use of Augmentative and Alternative Communication (AAC) in the Intensive Care Unit: a Scoping Review - Masruroh, Rurin; Trisyani, Yanny; Emaliyawati, Etika (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Patients in the Intensive Care Unit (ICU) often experience limitations in verbal communication due to ventilator use, sedation, or other medical conditions. These communication barriers can interfere with the delivery of medical information and affect the quality of patient care. Augmentative and Alternative Communication (AAC) is a potential solution to improve interactions between patients, healthcare providers, and families in the ICU environment. This review aimed to explore the implementation of AAC in the ICU, including its effectiveness, challenges, and impact on the quality of communication and patient care. This study used a scoping review approach following the PRISMA-ScR guidelines. A literature search was conducted through the EBSCOhost Medline, PubMed, and Google Scholar databases, using relevant keywords related to AAC and ICU. Studies that met the inclusion criteria were analyzed thematically to identify key findings. Of the 386 articles identified, 11 articles met the criteria for further analysis. The results showed that implementing AAC in the ICU can improve communication between patients and healthcare providers, reduce patient anxiety, and strengthen the therapeutic relationship. However, there are obstacles to its implementation, such as a lack of training for healthcare providers, time constraints, and a lack of institutional policies that support the systematic use of AAC. Despite the challenges in implementing AAC in the ICU, this technology has great potential to improve patient communication and quality of care. Therefore, a more comprehensive strategy is needed, including training health workers, developing institutional policies, and procuring communication devices that are appropriate to patient needs to support optimal implementation of AAC in the ICU. Keywords: Augmentative and Alternative Communication, ICU, Communication, Critical Care, Scoping Review.